A Study On Microteaching As Perceived By UTM TESL Undergraduates - Wan Zakaria, Wan Zarina (2010)
Microteaching is a compulsory subject to be taken before a student is allowed to go for the practical teaching. This indicates the importance of microteaching to prepare the future teacher trainees to teach in school. However, there are some students who take the subject for granted. Therefore, this research had been carried out to investigate the perception of Teaching English as Second Language (TESL) students in UTM regarding their microteaching course. 78 students from the third year and fourth year were chosen to become the respondents of this study. These respondents had completed their microteaching course and had done their teaching practice in the previous semesters. Each respondent was asked to answer a set of questionnaire consisted of 41 items regarding the microteaching experience. For ease of reference, the researcher divided the items in the questionnaire into four different sections which are demographic information of the respondents, opinion towards microteaching, factors affecting perception towards microteaching and application of the skills learnt in microteaching during teaching practice. The findings of the study indicated that the students have high level of perception towards microteaching.